(untitled) (Journal of the College of Education for Women, 2019)
Numerous academic and critical studies concerned with the language of poetry, with the differences and diversity in these studies and the critical methods. , the study tries to study this modern approach in the language Iraqi and Arabic poetry according to analyzing and following the functional dimension of the language, regardless of its poetic value which should be on them, as each poetic experience has its own language, thestudy came to investigate the variety of poetry samples, poets from different and far generations. - in an attempt to give an image Career dimension of language, the center of intellectual transformations that have affected the experience of Arabic poetry generally, and the level of language to be exact, as a tool for that experience, and poetry , is but the technical engine to invest those technical, psychological and intellectual potential in the language, and in both sides intellectual and language shifts - reflected the contribution of acculturation between language and community and what is reflected from that employment and the implications along the lines of linguistic structures .The study is about Iraqi poetry whichfalls on dimensions and several axes: Intertextuality, and participatory, and cynical, andFantasia, and complex "composite", and antagonistic "ironic", as well as employment of the setting of poetry language.